Perbaikan Kualitas Buah Jambu Biji (Psidium guajava L.) Kultivar Getas Merah melalui Aplikasi GA3, sebagai Upaya Meningkatkan Daya Saing Buah Lokal - NI NYOMAN ARI MAYADEWI; I MADE SUKEWIJAYA (Agrotrop : Journal on Agriculture Science, 2019)
Quality Improvement of Guava Fruit (Psidium guajava L.) “Getas Merah” Cultivar Through GA3 Application, as an Effort to Increase Local Fruit Competitiveness. This study aimed to improve the quality of fruit of Getas Merah guava, which reduces the content of fruit seeds by giving gibberellic acids (GA3). This research was conducted in Banjar Lawak, Bilok Sidan Village, Petang District, Badung Regency from July to November 2017. The area of guava plant used by farmers with rental system. Samples taken in the field and then analyzed at the Laboratory of Agronomy and Horticulture Faculty of Agriculture Udayana University. Analysis of chemical content of fruits carried out in Food Analysis Laboratory Faculty of Agricultural Technology Udayana University. This experiment was a one-factor experiment with GA3 concentration of six levels i.e. G0 = 0 ppm, G1 = 50 ppm, G2 = 100 ppm, G3 = 150 ppm, G4 = 200 ppm and G5 = 250 ppm. Each level of treatments was repeated 5 times. The results showed that there was a decrease of seed content in fruit of 9.24% (GA3 of 50 ppm), 13.99% (GA3 of 100 ppm), 46.33% (GA3 of 150 ppm), 48.92% (GA3 of 200 ppm), and 65.01% (GA3 of 250 ppm) when compared to controls. In this study the treatment of several levels of concentration can reduce the number of seeds, but can not make fruit without seeds.